2010
DOI: 10.1118/1.3455276
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modeling of lung motion over the entire respiratory cycle using measured pressure‐volume data, 4DCT images, and finite‐element analysis

Abstract: Purpose: Predicting complex patterns of respiration can benefit the management of the respiratory motion for radiation therapy of lung cancer. The purpose of the present work was to develop a patient-specific, physiologically relevant respiratory motion model which is capable of predicting lung tumor motion over a complete normal breathing cycle. Methods: Currently employed techniques for generating the lung geometry from four-dimensional computed tomography data tend to lose details of mesh topology due to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 54 publications
1
50
0
1
Order By: Relevance
“…In vivo experiments are required to fine-tune the pipeline parameters and ensure its reliability and rigor for clinical applications. Comparing the results obtained in this study with those reported by Eom et al [23] for modeling motion of the respiring lung over the entire respiratory cycle (maximum position error ¼ 5.8 mm; average position error ¼ 3.5 mm) indicates that our results are encouraging. Errors obtained in this investigation include error components from the image processing, experimental procedure and FE modeling of the pipeline.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In vivo experiments are required to fine-tune the pipeline parameters and ensure its reliability and rigor for clinical applications. Comparing the results obtained in this study with those reported by Eom et al [23] for modeling motion of the respiring lung over the entire respiratory cycle (maximum position error ¼ 5.8 mm; average position error ¼ 3.5 mm) indicates that our results are encouraging. Errors obtained in this investigation include error components from the image processing, experimental procedure and FE modeling of the pipeline.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, the biaxial tension test data used in the aforementioned work was obtained using old measurement instruments that lacked high precision, while the test data analysis involved significant sample geometry and boundary condition uncertainties. Due to the lack of other sources of lung tissue hyperelasticity data, Eom et al also used the same biaxial tension dataset in their recently presented lung biomechanical model [23]. They employed FEM to develop a respiratory motion model for predicting lung tumor motion over a complete normal breathing cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The results in Table 2 show that the explanatory variable of the lung volume had a significant difference in the 3D direction compared with the other explanatory variables, showing that the lung volume had a significant influence on the estimated lung tumor position. In current clinical practice, a single anatomical signal and a correspondence model between a single anatomical signal and a motion of the internal anatomy are typically used to reconstruct 4D-CT 14 and to estimate target position, [15][16][17] respectively. In addition, correspondence models have been used to improve image quality in 4D-CT image reconstruction.…”
Section: Comparison Of Internal Target Volumesmentioning
confidence: 99%
“…In this work, we focus on the link between tissue deformation and ventilation. Previous work of whole organ lung models has typically focused on modelling either ventilation or tissue deformation [1,2,3,4,5,6,7,8]. However, the two components are intrinsically linked; evaluating them separately does not necessarily provide an accurate description of lung function.…”
Section: Introductionmentioning
confidence: 99%